The Protective Effects of Shengmai Formula Against Myocardial Injury Induced by Ultrafine Particulate Matter Exposure and Myocardial Ischemia are Mediated by the PI3K/AKT/p38 MAPK/Nrf2 Pathway - Chen, Lina; Guo, Yuan; Qu, Shuiqing; Li, Kai; Yang, Ting; Yang, Yuanmin; Zheng, Zhongyuan; Liu, Hui; Wang, Xi; Deng, Shuoqiu; Zhang, Yu; Zhu, Xiaoxin; et al. (Frontiers in Pharmacology, 2021)
Background and Purpose: Ultrafine particulate matter (UFPM) induces oxidative stress (OS) and is considered to be a risk factor of myocardial ischemia (MI). Shengmai formula (SMF) is a traditional Chinese medicine with antioxidant properties and has been used to treat cardiovascular diseases for a long time. The aim of this study was to explore the protective role of SMF and the mechanism by which it prevents myocardial injury in UFPM-exposed rats with MI. Methods: An MI rat model was established. Animals were randomly divided into five groups: sham, UFPM + MI, SMF (1.08 mg/kg⋅d) + UFPM + MI, SMF (2.16 mg/kg⋅d) + UFPM + MI, and SMF (4.32 mg/kg⋅d) + UFPM + MI. SMF or saline was administrated 7 days before UFPM instillation (100 μg/kg), followed by 24 h of ischemia. Physiological and biochemical parameters were measured, and histopathological examinations were conducted to evaluate myocardial damage. We also explored the potential mechanism of the protective role of SMF using a system pharmacology approach and an in vitro myoblast cell model with small molecule inhibitors. Results: UFPM produced myocardial injuries on myocardial infarct size; serum levels of LDH, CK-MB, and cardiac troponin; and OS responses in the rats with MI. Pretreatment with SMF significantly attenuated these damages via reversing the biomarkers. SMF also improved histopathology induced by UFPM and significantly altered the PI3K/AKT/MAPK and OS signaling pathways. The expression patterns of Cat, Gstk1, and Cyba in the UFPM model group were reversed in the SMF-treated group. In in vitro studies, SMF attenuated UFPM-induced reactive oxygen species production, mitochondrial damage, and OS responses. The PI3K/AKT/p38 MAPK/Nrf2 pathway was significantly changed in the SMF group compared with that in the UFPM group, whereas opposite results were obtained for pathway inhibition. Conclusion: These findings indicate that SMF prevents OS responses and exerts beneficial effects against myocardial injury induced by UFPM + MI in rats. Furthermore, the PI3K/AKT/p38 MAPK/Nrf2 signaling pathway might be involved in the protective effects of SMF.